2015
DOI: 10.2147/ijn.s91631
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, optimization, and in vitro simulated inhalation delivery of carvedilol nanoparticles loaded on a coarse carrier intended for pulmonary administration

Abstract: Carvedilol (CAR) is a potent antihypertensive drug but has poor oral bioavailability (24%). A nanosuspension suitable for pulmonary delivery to enhance bioavailability and bypass first-pass metabolism of CAR could be advantageous. Accordingly, the aim of this work was to prepare CAR nanosuspensions and to use artificial neural networks associated with genetic algorithm to model and optimize the formulations. The optimized nanosuspension was lyophilized to obtain dry powder suitable for inhalation. However, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 57 publications
(64 reference statements)
1
17
0
Order By: Relevance
“…The measurements were performed after dilution. 18 The ZP evaluation was carried out by monitoring the electrophoretic movement of the particles in the electrical field. All measurements were performed in triplicate.…”
Section: Determination Of Ps Pdi and Zpmentioning
confidence: 99%
“…The measurements were performed after dilution. 18 The ZP evaluation was carried out by monitoring the electrophoretic movement of the particles in the electrical field. All measurements were performed in triplicate.…”
Section: Determination Of Ps Pdi and Zpmentioning
confidence: 99%
“…Thus, it can be concluded that the crystallinity of EE decreased because of its encapsulation by stabilizers. Data obtained from DSC failed to explain factual changes that occurred in drug crystals during processing [39] .…”
Section: : Photomicrographs Of Sem and Inverted Phase Microscopic Imamentioning
confidence: 96%
“…(X 1 ) was associated with increase in the average Mwt of Pluronics Õ mixture resulting in less kinetically restricted encapsulation process of the drug on Pluronic Õ surface so a less uniform distribution of PS (higher PDI) was obtained (Abdelbary et al, 2015). As for hydration volume (X 3 ), increased levels of phase volume ratio and water volume decreased the PDI.…”
Section: Particle Size (Ps) Polydispersity Index (Pdi) and Zeta Potmentioning
confidence: 99%